2020
DOI: 10.1590/0034-7167-2019-0686
|View full text |Cite
|
Sign up to set email alerts
|

Caring for cancer patients facing death: nurse's perception and experience

Abstract: Objective: To know the experiences and perceptions of nurses who care for dying cancer patients. Method: A descriptive, qualitative study, developed in a private hospital in Sao Paulo, with a total of nine nurses, aged between 24 and 46 years old, who participated in a semi-structured interview. Results: Through Bardin's Content Analysis, three categories were highlighted: Death as a natural process and the final stage of the life cycle; Although it is difficult, it is important to get emotionally involved w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 17 publications
0
4
0
1
Order By: Relevance
“…Funes, et al (2020) 19 identificou em seu estudo que a equipe de enfermagem que lida diariamente com questões relacionadas à terminalidade, em sua maioria, entende a morte como sendo um fenômeno complexo, doloroso e de difícil aceitação, principalmente quando se trata da área oncológica. No cotidiano de trabalho das equipes essa abordagem ainda é precária, sendo necessário tratar o tema junto às equipes multiprofissionais, oportunizando espaço para diálogo e com vistas a amenizar o sofrimento dos profissionais ao se depararem com tais situações.…”
Section: Discussionunclassified
“…Funes, et al (2020) 19 identificou em seu estudo que a equipe de enfermagem que lida diariamente com questões relacionadas à terminalidade, em sua maioria, entende a morte como sendo um fenômeno complexo, doloroso e de difícil aceitação, principalmente quando se trata da área oncológica. No cotidiano de trabalho das equipes essa abordagem ainda é precária, sendo necessário tratar o tema junto às equipes multiprofissionais, oportunizando espaço para diálogo e com vistas a amenizar o sofrimento dos profissionais ao se depararem com tais situações.…”
Section: Discussionunclassified
“…In this regard, Funes et al . [ 21 ] showed that nurses grieved over the death of their patients. It seems, the severity and extent of grief and sadness caused by the patient's death depend on several factors, including empathy, nurse–patient communication, and nurses' lower ability to control their emotions in the face of painful situations.…”
Section: Discussionmentioning
confidence: 99%
“…(2) Semi-structured interview survey: Using a preliminary questionnaire and an interview guide, the participants were encouraged to talk freely on the following questions. The main questions were (1) the actual state of education related to communication with cancer patients, (2) what the nurses told the participants about difficulties in communicating with terminally ill cancer patients, and (3) responses of participants when they were consulted by nurses about their difficulties. When multiple participants were selected from one hospital, those with more years of experience were asked about the education provided by the hospital, while those with less years of experience were asked about the education provided by the department they work for, such as the ward.…”
Section: Data Collection Proceduresmentioning
confidence: 99%
“…Due to the lack of psychological assessment of the Talk at a conference (5) Suggest that willing nurses discuss it at a conference Even if there are difficult cases, there are wards that hold a death conference and others that do not, so I call out to wards that do not hold conferences Discuss with everyone in training (2) Talk to nurses in other groups, share with everyone that they are responding in the same way, and discuss how to get involved, although there is no correct answer Teach by linking consultation cases to cases of decision-making support lectures to consider the patientʼs feelings patient, feelings of being stuck between the patient and the family, and inability to wait for the patient to sort out their feelings, the nurses are afraid of hurting the patient and worried that they cannot speak to encourage the patient to express their feelings; hence, they consulted the participants.…”
Section: Develop a Fear Of Communication Due To Their Desire To Avoid...mentioning
confidence: 99%
See 1 more Smart Citation